(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
Juan José Saer tells in the novel Nadie nada nunca the dissolution of the Enunciation instance. One of the narrative motive in that this topic reveals is the intersubjective relationship of intimacy. Among other topics, the novel tells the impossibility to set an intimacy bound between the bodies. Hence, it is possible to talk about an antiphenomenological narrative model. The own body as fundamental Enunciation instance doesn´t show itself as the original place of meaning. To bring to light this motive of corporal intimacy in the fictional universe of Nadie nada nunca this paper uses, as lecture criterion, the Heideggerian Concept of intimacy (Innigkeit).